Cultural perspectives on farmers' perceptions Mennonite-non-Mennonite farmers in Southwestern Ontario - Macintosh, Pamela J. (Truro , Nova Scotia, Canada Department of Humanities, Nova Scotia Agricultural College and Rural Research Centre, 1993)
An exploration of cultural differences between two types of farm communities--Mennonites and Non-Mennonites-- in Southwestern Ontario, with focus on quality of life satisfaction, community satisfaction, and community environment. A brief discussion of previous research on the subject precedes the study reported here. The study is based on a random sample of 82 respondent farmers. Analysis reveal some notable differences between Mennonite and Non-mennonite farmers. The Mennonites consistently show a stronger attachment to their community, accountable by a strong cultural identity through their religious base. Both sample group display average to high levels of satisfaction with the quality of their lives, although Mennonite farmers exhibit consistently higher levels
Rural Studies Working Papers No. 2
Keywords: Cultural differences; Cultural variations